2003
DOI: 10.1034/j.1600-0404.2003.00209.x
|View full text |Cite
|
Sign up to set email alerts
|

Response of thymectomy: clinical and pathological characteristics among seronegative and seropositive myasthenia gravis patients

Abstract: The response to thymectomy was similar between the two groups. It has been suggested that seronegative patients have a better prognosis, but our results show no differences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0
5

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 22 publications
1
19
0
5
Order By: Relevance
“…The present study is the first published study examining long‐term prognosis of AChR and MuSK antibody negative MG. A recently published short‐term study showed no difference in the outcome of AChR antibody negative and positive MG, but the patients were followed up for 3 years only (Guillermo et al. , 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The present study is the first published study examining long‐term prognosis of AChR and MuSK antibody negative MG. A recently published short‐term study showed no difference in the outcome of AChR antibody negative and positive MG, but the patients were followed up for 3 years only (Guillermo et al. , 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Some patients are false negative as they have low affinity AChR antibodies not detected by standard assays [34], whilst others have MuSK and possible other still undetected antibodies. A retrospective cohort study displayed a similar post‐operative course in AChR antibody‐negative and AChR antibody‐positive patients with a follow‐up of at least 3 years [35]. Remission or improvement after TE occurred in 57% of AChR antibody‐negative patients and in 51% of AChR antibody‐positive patients.…”
Section: Myasthenia Gravis (Mg)mentioning
confidence: 97%
“…The immune response exposes additional antigens widening the autoimmune process (epitope spreading). 9 Proposed mechanisms for favorable response after thymectomy include elimination of the source of continued antigenic stimulation (considering the expression of the alpha subunit of AChR in the thymus as a source of auto-antigen), removal of a reservoir of B cells that secrete AChR antibodies, correction of a disturbance of immune regulation in MG. 10 Besides anti-AChR synthesizing B cells the thymus is also suggested to harbor clonally restricted T cells specific for AChR epitopes that regulate the immune response and induce antibody production in MG. 11−13 The benefit from thymectomy is usually unlikely in seronegative patients and/or late-onset MG. 2,14 Thymomas are well known to be associated with various autoimmune disorders. The pathological basis for the autoimmune process remains obscure.…”
Section: Discussionmentioning
confidence: 99%